Dry eye disease and psychosomatics—benefits of mind-body therapy for dry eye disease - Zhao, Cong; Li, Xiang (Frontiers in Medicine, 2025)
Dry eye disease (DED) is a chronic inflammatory condition with increasing prevalence. Current treatment strategies, including artificial tears and anti-inflammatory agents, often fail to fully relieve ocular discomfort or meet patients’ broader clinical needs. Psychosomatic medicine is grounded in the biopsychosocial model of disease. Epidemiological studies suggest that DED is influenced by a range of physiological, psychological, and social factors. Psychoneuroimmunology (PNI) may play a key role in the interplay between DED and mental health. Therefore, DED may be a psychosomatic disease, and its management should follow a multifaceted approach that considers both molecular-level mechanisms and broader psychosocial factors. The efficacy of mind-body therapies (MBT) in psychosomatic disorders has been widely recognized in recent years, yet there is still a wide scope for exploration in DED. This review explores the psychosomatic aspects of DED, highlights its subjective symptom burden, and discusses the potential benefits and mechanisms of MBT as an adjunctive therapy, offering new perspectives for its comprehensive management.